232k views
1 vote
Solve the initial-value problem y = 24 – 3yy(1) = 1.

User Govil
by
5.8k points

1 Answer

5 votes

Answer:


y = 8 -7e^(-3(x-1))

Explanation:

Assuming that the equation is
y '= 24 -3y with initial condition
y(1) = 1. We have,


(dy)/(dx) + 3y = 24, hence we can say that
P (x) = 3 and
Q (x) = 24 in the general form of the first order linear differential equation:


(dy)/(dx) + P(x)y = Q(x)

The integrating factor is given by:


e^{\int{3} \, dx } = e^(3x). Thus, multiplying the entire equation by the integrating factor:


e^(3x)(dy)/(dx) + 3e^(3x)y = 24e^(3x). This means that:


(d[e^(3x)y])/(dx) = 24e^(3x)


e^(3x)y = 8e^(3x) + C then


y = 8 + Ce^(-3x). Applying the initial condition:


C = -7e^(3) and therefore,
y = 8 -7e^(-3(x-1))

Assuming that the equation is
y = 24 -3y' with initial condition
y(1) = 1. We have,


(dy)/(dx) + (1)/(3)y = 8, hence we can say that
P (x) = (1)/(3) and
Q (x) = 8 in the general form of the first order linear differential equation:


(dy)/(dx) + P(x)y = Q(x)

The integrating factor is given by:


e^{\int{(1)/(3)} \, dx } = e^{(x)/(3)}. Thus, multiplying the entire equation by the integrating factor:


e^{(x)/(3)}(dy)/(dx) + (1)/(3)e^{(x)/(3)}y = 8e^{(x)/(3)}. This means that:


\frac{d[e^{(x)/(3)}y]}{dx} = 8e^{(x)/(3)}


e^{(x)/(3)}y = 24e^{(x)/(3)} + C then


y = 24 + Ce^{-(x)/(3)}. Applying the initial condition:


C = -23e^{(1)/(3)} and therefore,
y = 24 -23e^{-(1)/(3)(x-1)}

User Arnaud Jeansen
by
6.0k points